Development of Canva-based e-modules in the Project Based Learning model to improve the speaking skills of students at SMAN 1 Bintan Timur - Sigalingging, Saipul; Zaitun, Zaitun; Kumalasari, Tety; Abdulhajar, Encik; Nevrita, Nevrita; Irawan, Dody (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This study aims to develop a Canva-based e-module using the Project-Based Learning (PjBL) model to improve students' speaking skills in English lessons at SMA Negeri 1 Bintan Timur. This study was motivated by students' low english speaking skills and the limited availability of interesting and interactive teaching materials. The research method used was Research and Development (R&D) with the ADDIE development model, which consists of five stages, namely analysis, design, development, implementation, and evaluation. Based on the needs analysis, it was found that students and teachers needed digital teaching materials that were interesting, easily accessible, and interactive to improve students' speaking skills. The Canva-based e-module product was designed in accordance with the PjBL stages, which encourage students to actively engage in real projects and communicate using English. Initial test results show that the Canva-based e-module has an attractive appearance, is easy to use, and can motivate students to learn to speak more actively. Thus, the development of this e-module is expected to be an effective alternative teaching material in improving students' speaking skills in secondary schools.